2021
DOI: 10.1007/s10067-020-05538-x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric inflammatory multisystem syndrome (PIMS) presenting with retropharyngeal phlegmon mimicking Kawasaki disease

Abstract: There have been several recent reports of children presenting with severe multisystem inflammatory syndrome (PIMS) resembling complete or incomplete Kawasaki disease (KD) during COVID19 pandemic. Being a novel disease, limited data is available for its identification and management. We report a child presenting with fever, neck swelling, and generalized edema, who was diagnosed as PIMS. MRI neck showed retropharyngeal phlegmon resembling similar finding in KD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…11 Additional case reports and series demonstrated similar findings. 1222 Our case and review of other reported cases strengthens the evidence of association between retropharyngeal inflammation and MIS-C. Absence of an association of retropharyngeal inflammation and MIS-C in the literature might have led to a relatively late diagnosis in some patients such as occurred with our patient.…”
Section: Discussionsupporting
confidence: 83%
“…11 Additional case reports and series demonstrated similar findings. 1222 Our case and review of other reported cases strengthens the evidence of association between retropharyngeal inflammation and MIS-C. Absence of an association of retropharyngeal inflammation and MIS-C in the literature might have led to a relatively late diagnosis in some patients such as occurred with our patient.…”
Section: Discussionsupporting
confidence: 83%
“…[19][20][21] To date there have only been anecdotal case reports reporting deep neck infection in children associated with SARS-CoV-2. [11][12][13][14]22 In our cohort, 13.5% of patients had cervical manifestation as a primary presentation.…”
Section: Discussionmentioning
confidence: 65%
“… 1 , 8 , 9 , 10 There were anecdotal reports of MIS‐C presenting with prominent cervical manifestations. 11 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Some researchers consider that the retropharyngeal abnormalities in KD are presumably linked to the vasculitis of microvessels that cause oedema and in ammation, which is a non-infectious in ammatory reaction. [11][12][13] But some researchers consider that the infection of some bacteria such as staphylococcal and streptococcal toxin as superantigens may be involvement in the pathogenesis of KD.…”
Section: Discussionmentioning
confidence: 99%